India recuatis democracy - "Ghurye, G. S." (Bombay, 1978)
This book as the third unit of my trilogy on Indian political society. The first was published in 1968. As its title Social Tensions in India indicates, it dealt with social tensions, but with only some of them, that occurred in the Indian polity.
Keywords: Democracy - India